Changes in clinicopathological profile post Trans-sphenoidal surgery in patients with Pituitary Adenomas: An Institute based study from North East India - Mookherjee, Hirak; Gupta, Vijay Kumar; Attry, Sanjeev (Nepal Journal of Neuroscience, 2020)
Introduction: Pituitary adenomas are common intracranial neoplasms. In this study, we report the changes in clinical features and hormone profile in patients of pituitary adenoma following transsphenoidal surgery. Patients and methods: Thirty consecutive cases of pituitary adenoma diagnosed and operated at Bangur Institute of Neurosciences, West Bengal, India were followed up for clinical and hormonal profile resolution following trans-sphenoidal surgery between December 2010 and November 2012. The patient group included 14 female and 16 male patients and the mean age of patients was 35.86 years (range: 14–58 years). Results: Fifteen (50%) cases were non-functioning adenomas. Among the hormonally active pituitary adenoma, prolactin-producing adenomas were most common (66.67%), followed by growth hormone-producing adenomas (20%) and adrenocorticotrophic hormone-producing adenomas (13.33%). The most common symptom was headache and visual disturbances. Menstrual disturbances and galactorrhea were observed in six and two females respectively out of the 14 females in the study participants. Resolution of symptoms was reported by majority of our patients and hormonal derangement was corrected in 30% of our study subjects. Conclusion: We report 30 patients with pituitary adenoma who underwent surgery. Resolution of clinical symptoms and endocrine functions was observed in the majority of our patients.